2001
DOI: 10.1007/s001980170100
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Body Composition in Ulcerative Colitis: A Six-Year Follow-up

Abstract: Reduced bone mineral density (BMD) has been reported in ulcerative colitis (UC), but there are no data concerning body composition (fat and lean mass) in such patients. We used whole body dual-energy X-ray absorptiometry (Hologic QDR 1000 W) at baseline and after 6 years of follow-up to study bone density, and fat and lean mass in 43 outpatients with mild UC (21 men, mean age 36 years, range 21-57 years, and 22 women, mean age 35 years, range 23-45 years at baseline; disease extent: 2 proctitis, 18 proctosigmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…BMD was found to negatively correlate with disease duration and inflammatory markers and to positively correlate with vitamin D levels . At longitudinal follow‐up in one study, female UC patients demonstrated a negative correlation with steroid use with regard to total body and lumbar spine BMD …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMD was found to negatively correlate with disease duration and inflammatory markers and to positively correlate with vitamin D levels . At longitudinal follow‐up in one study, female UC patients demonstrated a negative correlation with steroid use with regard to total body and lumbar spine BMD …”
Section: Resultsmentioning
confidence: 99%
“…In one study of UC patients, the female cohort was found to have reduced FFM compared with controls at baseline ( n = 22) . After 6‐year longitudinal follow‐up of this group of female patients, there was no significant decrease in total FFM compared with controls, as their limb FFM was found to have increased relative to baseline measurements …”
Section: Resultsmentioning
confidence: 99%
“…Longitudinal studies on the rate of changes in bone mineral density (BMD) in IBD patients over time are few and have yielded conflicting results. Both increased bone loss and no significant changes in BMD during follow-up have been reported (4)(5)(6).…”
mentioning
confidence: 86%
“…4,[22][23][24] Malnutrition is especially common in active UC patients after long-term hospitalization; 11,25 however, few studies have evaluated the nutritional status in patients with UC during remission. 4,12,26,27 Only one trial found a more compromised nutritional status (body weight and BMI) in UC patients during remission than in a control group. 28 In our study, we identified a low incidence of calorie malnutrition.…”
Section: Discussionmentioning
confidence: 99%